IDENTIFICATION OF BACTERIAL GENERA PRESENT IN RAINBOW TROUT (ONCORHYNCHUS MYKISS) CULTIVATED IN SANTA CATARINA HIGHLANDS - Schäfer, Ingelore; Rohrbacher, Luciana de Oliveira; Colla, Nilse Carolina (Revista de Ciências Agroveterinárias, 2004)
Intensive cultivation systems have changed Santa Catarina fish culture into an activity providing good economical returns for growers. However, little is known about diseases that attack aquatic organisms. This work aimed at studying the occurrence of Yersinia ruckeri, Aeromonas salmonicida and Flavobacterium columnare causing acute diseases in trouts and also identifying possible bacteria present in organs of apparently helthy trouts. In the period of August 2002 – July 2003, 30 trout livers and kidneys were monthly examined from three fish farms. At fish collection, data were recorded on temperature, pH, ammonia and dissolved oxygen in tank water. At laboratory, trouts were sacrificed and necropsied with the purpose of analysing their internal and external structures. The liver and kidney samples were seeded on plates containing Cytophaga Agar, Shotts-Waltman Agar, TSA supplemented with 7% cattle blood, Mac Conkey Agar, and incubated at 25oC up to four days. The values found in water analysis were considered appropriate for trout cultivation. The identification of isolated organisms was performed by Bac-Tray miniaturized system (Inlab) and API (bioMérieux). The samples analysed did not reveal the presence of Y. ruckeri, A. salmonicida, and F. columnare, but isolated some other potentially pathogenic bacteria: Aeromonas hydrophyla (3.0%), Plesiomonas shigelloides (2.5%), Hafnia alvei (0.6%) and Edwarsiella tarda (0.3%). The remaining bacterial agents isolated are not described in literature as disease in fishes. As for the rate of infected trouts, Fish Farm A recorded 19.2% , whereas B and C scored 16.7%.